Projetos interdisciplinares no ensino de química para o ensino médio: o que dizem os professores? - Gabrielle Cristina Moreira Barbosa (2019)
This work is the result of a reflection carried out with a group of five chemistry teachers working in public schools in the municipality of Santa Luzia, in Minas Gerais, on the work with this discipline from the perspective of interdisciplinary projects. The general objective of the work is to investigate what the professors of chemistry say about the interdisciplinary approach in teaching this discipline in the city of Santa Luzia, focusing on daytime high school. The research is configured in a case study, and is carried out using the following instruments: semi-structured interviews, classroom observation, questionnaire application and three discussion groups with the teachers participating in the previous stages. The results obtained show that there is no consensus on the concept of interdisciplinarity and this is not well understood by teachers. Regarding the interdisciplinary approach in the teaching of Chemistry, the research points out that there are many ways to achieve it. The group participating in this work agrees that the realization of interdisciplinary projects is a good teaching strategy, when well planned, as long as there is no distancing from the theoretical contents in its execution. As a final product of this research, two interdisciplinary didactic sequences have been improved and are available in the addendum to this work.